Impressionistic Description in Woolf's Works: Application and Limitation of Modernist Aesthetics - Shou, Ruoan (International Journal of Social Sciences and Public Administration, 2024)
As a representative writer of modernist literature and feminist literature in the 20th century, Virginia Woolf's works profoundly reflect the complexity of modern society and the unique perspective of women. Through the analysis of works such as Mrs. Dalloway, To the Lighthouse, Orlando and A Room of One's Own, this paper explores Woolf's narrative innovation under the trend of modernist thought and her redefinition of gender roles. The study found that Woolf skillfully combined modernist techniques such as stream of consciousness with feminist ideas to show the themes of gender fluidity and self-exploration. However, despite her breakthroughs in narrative style and character creation, the complexity of Woolf's works also brought challenges in understanding and acceptance. This paper summarizes her achievements and limitations in modernist aesthetics and emphasizes the important influence of these works on modern literature and feminist theory.